RESEARCH ON THE HARMFUL EFFECTS AND COMPLICATIONS OF NICOTINE ON THE ADOLESCENT BODY (International Scientific Journal Alfraganus, 2025)
Uzbek culture is characterized by the promotion of a healthy lifestyle among the youth. In particular, engaging young men and women in sports, education, the arts, and music is a long-standing tradition of our people. The older generation bears direct responsibility for the future of the youth — not only their parents, but also other senior family members, teachers, coaches, and the mahalla (community). It is important to highlight the role of the state in this matter. For the past five years, initi- atives proposed by the President of Uzbekistan, Shavkat Mirziyoyev, aimed at creat- ing additional opportunities for the education and upbringing of young people and increasing women's employment, have been implemented in the educational pro- cess. These initiatives include fostering interest among youth in music, the arts, 14 ALFRAGANUS xalqaro ilmiy jurnal https://journals.afu.uz/ ISSN: 2992 - 8974 № 2 (13). 2025 literature, theater, and other forms of culture, expanding their involvement in sports, creating the necessary conditions for this, promoting effective use of computer tech- nologies and the internet by the population and youth, enhancing spiritual develop- ment, promoting reading, and ensuring women’s employment. This confirms that the proper upbringing of young people is under close attention by the state. Today, smoking among adolescents is a global issue, negatively affecting their mental and physical abilities. In this regard, the present article presents research findings on the harmful effects and complications of nicotine on the adolescent body. It examines the impact of nicotine on acetylcholine receptors, its molecular basis, as well as its metabolism. Conclusions are drawn regarding the crucial role of the state in the upbringing of the younger generation.
Keywords: medicine; pharmacology; treatment; alkaloids; nicotine; adoles